SOCIO-ECONOMIC AND ENVIRONMENTAL ATTRIBUTES OF WASTE ELECTRICAL AND ELECTRONIC EQUIPMENT (WEEE) RECYCLING IN ASIA - Menikpura, S; Hotta, Yasuhiko; Santo, Atsushi; Jain, Amit (MATTER: International Journal of Science and Technology, 2016)
Due to ever increasing demand, the electronics industry has been growing at a rapid pace, and therefore handling and management of Waste Electrical and Electronic Equipment (WEEE) has become one of the key problems in the modern world. Improper handling and management of WEEE in developing countries can cause a huge environmental damage and threats on human health. In some developed countries, policies have been set up and strategies have been implemented by aiming recuperation of materials from WEEE while conserving resources and controlling environmental pollution. For instance, in Japan, the home appliance recycling law like strategies have been implemented for achieving a recycling-oriented society. In this study, socio-economic and environmental effects from end-of-life home appliances recycling such as washing machines, Refrigerators, Air conditioners and Televisions have been assessed. Recycling mechanism of end-of-life home appliances in Fokuoka Prefecture under Japan’s home appliances recycling law was evaluated via life cycle assessment perspective. Life cycle based methodology was developed for the assessment considering all the phases life cycle of WEEE recycling such as collection, primary and secondary transportation, pre-processing (dismantling), recycling and material recovery. Net greenhouse gas (GHG) emission and net resource savings potentials were quantified as the key indicators to measure the major environmental impacts while green jobs creation potential and income based community well-being was quantified to assess the socioeconomic attributes of end-of-life home appliances recycling. Further, recycling mechanism in India was assessed and the results obtained from the case studies was compared for identifying the most appropriate approach of recycling and then for supporting policy making process. In the case of Japan, the results demonstrated that it would be possible to avoid more than 50% of GHG emissions and 55-80% of abiotic resource consumption as for all kind WEEE recycling that would some way or another happen through the production of the equivalent amount of materials from conventional processes. Further, 165 employment opportunities have been created and an annual income of 686 million Japanese yen can be generated due to handling and managing of 700,000 units of WEEE. In the case of India WEEE management activities are shown lower GHG emissions potential from recycling process and therefore, it would positively contribute for more GHG savings and fossil resource savings by recuperating significant amount of materials from WEEE. The authors argue that this kind of tangible information will be helpful for decision and policy-making process and for strengthening and implementing a set of comprehensive policies and legislation for achieving a recycling-oriented society in Japan as well as other countries.